The Effect of Using Acne Creams Containing Steroids on the Appearance of Inflammatory Acne - Puguh Riyanto; Devina Adiyani Pranowo; Cindy Cindy; Leoni Agnes (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Acne vulgaris is common in adolescents and young adults and can decrease quality of life. Self-medication with creams containing topical corticosteroids is still prevalent and has the potential to trigger inflammatory acne. Objective: This study assessed the relationship between exposure to steroid-containing creams and the appearance of inflammatory acne. Methods: A cross-sectional observational study was conducted among adolescents and young adults aged 15–41 years with acne complaints, recruited via an online questionnaire using consecutive sampling (n = 110). Topical steroid exposure (yes/no) and inflammatory acne occurrence (yes/no, assessed using reference lesion images) over the past 3 months were the primary independent and outcome variables, respectively. The association was evaluated using the Pearson chi-square test, with prevalence ratio (PR) and 95% confidence interval (CI). Results: Of 110 subjects (mean age, 22.95 years; 54.5% female), 28.2% reported topical steroid exposure and 69.1% had inflammatory acne. The proportion of inflammatory acne was significantly higher in the exposed group (90.3%) than in the unexposed group (55.7%), with a PR of 1.62 (95% CI, 1.28–2.06; p = 0.001). The dominant symptoms in the inflammatory acne subgroup were a burning/heat sensation (56.6%) and pain (50.0%). Conclusion: Topical steroid exposure was significantly associated with inflammatory acne in this population. These findings underscore the need to avoid unsupervised use of steroid-containing anti-acne creams. The cross-sectional design limits causal inference; therefore, prospective studies with clinical confirmation and control of confounding factors are warranted.